Impact of floods on food security in rural Afghanistan - Yolchi, Jamshid; Wang, Huaiyu; Pede, Valerien (Elsevier, 2024)
Floods, affecting roughly one million Afghans annually and causing substantial economic losses, is one of the most frequent disasters. This study examines the impacts of floods on household food security in rural Afghanistan, where 80 % of the population relies on subsistence farming and consists of 80 % of the food-insecure population. Based on the 2022 Data in Emergency Monitoring Round 5 dataset, a two-stage least squares with an instrumental variable is applied to analyze the relationship, considering district altitude and unconditional aid. Our findings reveal the negative impacts of floods, i.e., flood exposure decreases the Food Consumption Score (FCS) by 7.1 points and the Household Dietary Diversity Score (HDDS) by 0.14 points. Additionally, flood exposure increases the Household Hunger Scale (HHS) by 0.77 points and significantly raises the probability of moderate and severe food insecurity by 11 % and 20 %, respectively. Food aid offers a lifeline, boosting FCS by 1.54 points and reducing HHS by 0.42 points while mitigating food insecurity risks. High-altitude areas experience greater vulnerability, with higher hunger levels and lower dietary diversity compared to lowlands. Our research suggests prioritizing preventative strategies like area-based policies and flood preparedness plans over solely relying on post-disaster relief initiatives. Additionally, accounting for topographical variations, at least at the district level, is crucial for future food security studies in Afghanistan and similar contexts. These findings hold significant implications for achieving UN Sustainable Development Goals 2 (Zero Hunger) and 13 (Climate Action).